Development of Prototype : Fish Drying Electronic Roof - Abd Latif, Mohd Nasrulddin; Abd Aziz, Nurul Ashykin; Ramdan, Mohamad Rohieszan; Othman, Nor Hafiza (Multidisciplinary Applied Research and Innovation, 2022)
The fishing industry is an important part of the national economy. Basically, local fishing communities that produce fish -based products often face difficulties throughout the drying process. This problem is due to the hot climate change and rainy weather experienced by Malaysia throughout the year. Therefore, they need to monitor the fish drying process to ensure that the products produced are able to meet the needs of customers. This has led to an experimental prototype design of the "Fish Drying Electronic Roof," which will use a pulling machine that can go in when the weather is rainy and out when the weather is hot. As a result, the resulting project successfully produced machines that can help ease the burden on fish product operators even if they are out of the area. Finally, this project can provide guidance and thoughtful ideas to stakeholders through the creativity and innovation projects it produces.